Research of auxiliary supporting means in swimming training of adults, which are afraid of water - Шейко Лілія Вікторівна (Liliya Sheyko) (Slobozhanskyi Herald of Science and Sport, 2015)
Purpose: to consider the possibility of effective teaching swimming adults suffering from hydrophobia, using auxiliary equipment. Materials and Methods: the study involved 37 people aged 22–45 years. Applied: analysis of the educational process of learning to swim, questioning, peer review techniques, teacher observation and experiment, mathematical statistics. Results: this study suggests that the formation of swimming skills is faster and more effective when used the auxiliary equipment. In the experimental group, four swimming styles were mastered by 59% and in the control by 18%. Conclusions: the proposed method of training of adults, with auxiliary equipment, allows to overcome the feelings of fear, accelerates the learning process and improve its efficiency